Self-Sufficiency versus Theosufficiency - ESSO, JEAN CHRISTIAN (Fakultas Filsafat Universitas Advent Indonesia, 2024)
This article entitled: ‘self-sufficiency versus theosufficiency analyzes the notion of self-sufficiency. Notion which has become so valued to our economies, churches and to communities. This concept, although functionally attractive, does not do justice to the nature of the church which far from being an autonomia is a koinomia and theonomia. The article proposes a semantic reappropriation of the nature of the expression in relation to the ontological reality of the body of Christ. The autonomy or self-sufficiency in question in this study refers to the interdependence between a lower structure and another higher one which serves as supervision. This work which compares two concepts and which attempts to situate self-sufficiency in an ecclesiological and theological context will have allowed us to highlight two types of self-sufficiency. Firstly, anthropocentric self-sufficiency: This is what we can call atheistic economics; a kind of humanism centered on the search for vital balance by oneself and secondly theocentric self-sufficiency : where it is God who dictates the attitude to follow and ensures the vital balance “autarkeia” which would therefore be assimilated to a form of Theo-dependence dear to church theocentrism.